2009
DOI: 10.1007/s12640-009-9092-3
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Local Anesthetic Activity of Neosaxitoxin with Bupivacaine or Epinephrine: Development of a Long-Acting Pain Blocker

Abstract: Local anesthetics effectively block and relieve pain, but with a relatively short duration of action, limiting its analgesic effectiveness. Therefore, a long-acting local anesthetic would improve the management of pain, but no such agent is yet available for clinical use. The aim of this study is to evaluate the potentiation of the anesthetic effect of neosaxitoxin, with bupivacaine or epinephrine in a randomized double-blind clinical trial. Ten healthy males were subcutaneously injected into the left and righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 47 publications
0
22
0
1
Order By: Relevance
“…Given the intense interest in human Na v 1.7 as a target for pain (4)(5)(6)(7)15) and growing interest in clinical applications of guanidinium toxins as antinociceptive agents (16)(17)(18)(19)(20)(21)(22)(23), we began a series of electrophysiology recordings with TTX, STX, and gonyautoxin-III (GTX-III) against recombinant hNa v 1.7 α-subunit expressed in CHO cells. For comparative purposes, an identical series of measurements was made using rat Na v 1.4 (CHO).…”
Section: Resultsmentioning
confidence: 99%
“…Given the intense interest in human Na v 1.7 as a target for pain (4)(5)(6)(7)15) and growing interest in clinical applications of guanidinium toxins as antinociceptive agents (16)(17)(18)(19)(20)(21)(22)(23), we began a series of electrophysiology recordings with TTX, STX, and gonyautoxin-III (GTX-III) against recombinant hNa v 1.7 α-subunit expressed in CHO cells. For comparative purposes, an identical series of measurements was made using rat Na v 1.4 (CHO).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of several site 1 toxins in animals 8,14,15 and a study of neoSTX-bupivacaine and neoSTX-epinephrine combinations for subcutaneous infiltration in human volunteers 30 indicated that combination formulations involving a site 1 toxin such as neoSTX plus either bupivacaine or epinephrine produce more intense and more prolonged analgesia compared with neoSTX alone. Future clinical trials of such combinations are planned.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand NeoSTX has a selective blocking effect over NA V 1.2 [10,11]. This pharmacodynamical difference can explain the long lasting effect of NeoSTX that provides analgesia for over 24 h in animals and human volunteers [12,13]. …”
Section: Introductionmentioning
confidence: 99%